Preparation of Puerarin Chitosan Oral Nanoparticles by Ionic Gelation Method and Its Related Kinetics - Jie Yan; Zhi-Yu Guan; Wei-Feng Zhu; Ling-Yun Zhong; Zhuo-Qi Qiu; Peng-Fei Yue; Wen-Ting Wu; Jing Liu; Xiao Huang (MDPI AG, 2020)
In this paper, as an active ingredient, puerarin chitosan nanoparticles (Pur-CS/TPP-NPs) are prepared by an ionic gelation method. The chitosan (CS) concentration, pH of the CS solution, sodium tripolyphosphate (TPP) concentration, stirring speed, stirring time, ultrasonic power, and dosage are used as single factors for investigation, and the encapsulation efficiency, drug loading capacity, particle size, and polydispersity index (PDI) are used as indicators for investigation. The optimal prescription is determined using the Box−Behnken effect surface design method. The characterization of the best formulation, which is determined via an in vitro release assay and liquid chromatography/tandem mass spectrometry (LC-MS/MS) analysis methods, is used here for pharmacokinetic studies. An in situ single-pass intestinal perfusion model is used to investigate drug absorption in the intestine. After characterization, the morphologies of the nanoparticles are intact. It can be seen from the in vitro release experiments that the equation fitted by the nanoparticles is the Higuchi model, the nanoparticle release process is very stable and without sudden release, indicating that the nanoparticles are well-released in vitro. The pharmacokinetic results and the in situ single-pass intestinal perfusion model study show that the bioavailability and absorption of Pur-CS/TPP-NPs were significantly higher than Pur. Thus, all the results show that the prepared nanoparticles can significantly improve the bioavailability of Pur, and we hope to lay the foundation for the development of new products of Pur.